Concert Hall Sound Clarity: A Comparison of Auditory Judgments and Objective Measures - MIŚKIEWICZ, Andrzej; ROGALA, Tomira; ROŚCISZEWSKA, Teresa; RUDZKI, Tomasz; FIDECKI, Tadeusz (Archives of Acoustics, 2012)
The purpose of the study was to compare auditory judgments of sound clarity of music examples recorded in a concert hall with predictions of clarity made from the impulse response signal recorded in the same hall. Auditory judgments were made with the use of two methods: by rating sound clarity on a numerical scale with two endpoints, and by absolute magnitude estimation. Results obtained by both methods were then compared against the values of clarity indices, C80 and C50, determined from the impulse response of the concert hall, measured in places in which the microphone was located during recording of music examples. Results show that auditory judgments of sound clarity and predictions made from the C80 index yield a similar rank order of data, but the relation between the C80 scale and perceived sound clarity is nonlinear. The data also show that the values of C80 and C50 indices are in very close agreement.